Neurodevelopmental Disabilities in Canadian Children: Prevalence Data from the National Longitudinal Study of Children and Youth - Prasad, Asuri Narayan; Corbett, Bradley (Journal of Pediatric Neurology, 2019)
Aim Using population surveys of chronic health conditions, the present study aimed to examine changing trends in the prevalence of neurodevelopmental disabilities (NDD) with age and determine population-based estimates of prevalence and census-based estimates of absolute numbers of affected children.Methods We analyzed data from three cycles (1994–1999) of Canada's National Longitudinal Survey of Children and Youth (NLSCY) (Statistics Canada Survey).Results Cross-sectional prevalence rates for chronic NDD in children from birth to 15 years across cycle 1 to 3 of the NLSCY show an increasing trend over the years from 1994 to 1999. Population-based estimates were also calculated from census data. Weighted prevalence rates for four conditions in children aged birth to 15 years increased across the three cycles, except for cerebral palsy. Prevalence estimates in cycle 3 were: epilepsy 5.26/1,000 (95% confidence interval [CI]: 5.01, 5.52), cerebral palsy 2.81/1,000 (95% CI: 2.62, 2.99), intellectual disability 4.77/1,000 (95% CI: 4.53, 5.02), and learning disability 57.06/1,000 (95% CI, 56.36, 57.76). A male gender preponderance was noted for each NDD using logistic regression.Interpretation Prevalence rates of NDD in Canadian children show an incremental trend across three cycles in four conditions covered in the survey. The changing trends over the three cycles are discussed.
Keywords: neurodevelopmental disabilities; children; population; prevalence